2021
DOI: 10.3390/antiox10050714
|View full text |Cite
|
Sign up to set email alerts
|

Plant Foods Rich in Antioxidants and Human Cognition: A Systematic Review

Abstract: Oxidative stress can compromise central nervous system integrity, thereby affecting cognitive ability. Consumption of plant foods rich in antioxidants could thereby protect cognition. We systematically reviewed the literature exploring the effects of antioxidant-rich plant foods on cognition. Thirty-one studies were included: 21 intervention, 4 cross-sectional (one with a cohort in prospective observation as well), and 6 prospective studies. Subjects belonged to various age classes (young, adult, and elderly).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 104 publications
1
27
0
2
Order By: Relevance
“…Studies in individuals and animals have demonstrated that consumption of a high fat and sugar diet causes inflammation which spread into the brain, affecting key components of cognition [ 1 ]. Several factors have been involved in the development of cognitive dysfunction, including dysbiosis in the gut microbiota [ 2 ], increase in oxidative stress in the central nervous system [ 3 ], and possibly other metabolic abnormalities in other organs of the body, particularly in the liver. In obesity, which is often associated with consumption of a high fat and sugar diet, an imbalance in the gut microbiota was found to be associated with impaired gut barrier function and translocation of lipopolysaccharide (LPS) and inflammation in various tissues, such as liver, adipose, and brain tissue [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in individuals and animals have demonstrated that consumption of a high fat and sugar diet causes inflammation which spread into the brain, affecting key components of cognition [ 1 ]. Several factors have been involved in the development of cognitive dysfunction, including dysbiosis in the gut microbiota [ 2 ], increase in oxidative stress in the central nervous system [ 3 ], and possibly other metabolic abnormalities in other organs of the body, particularly in the liver. In obesity, which is often associated with consumption of a high fat and sugar diet, an imbalance in the gut microbiota was found to be associated with impaired gut barrier function and translocation of lipopolysaccharide (LPS) and inflammation in various tissues, such as liver, adipose, and brain tissue [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a crosstalk between adipose tissue and the brain was suggested to contribute to cognitive deficits [ 6 ]. Several dietary guidelines have focused on the consumption of antioxidant-rich plant foods, which may be effective in maintaining cognitive health [ 3 ]. Thus, the purpose of the present work was to develop a combination of functional foods that included nopal, soy protein, turmeric, and chia seed oil (bioactive foods) to modulate gut microbiota and enhance antioxidant activity to improve cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Oat groats were added to the test food to serve as a source of beta-glucan that could reach the colon and be fermented by saccharolytic microbes. The fiber blend of broccoli and tomato pomace was to serve as a source of natural antioxidant polyphenols known to have a protective effect against age-associated cognitive decline [17,18]. Both foods were supplemented with vitamins, minerals, and palatability enhancers.…”
Section: Animals Study Foods and Experimental Designmentioning
confidence: 99%
“…An attractive alternative to the development of small-molecule inhibitors of IDE is a nutritional strategy that implicates polyphenols. Polyphenols are naturally occurring compounds that possess antioxidant [ 18 , 19 , 20 ], anti-inflammatory [ 19 , 20 , 21 ], and anti-amyloidogenic [ 22 ] properties. As such, polyphenols have been hypothesized to prevent T2D [ 23 ] and AD [ 24 ].…”
Section: Introductionmentioning
confidence: 99%